Staphylococcus aureus forms spreading dendrites that have characteristics of active motility - Pollitt, Eric J.G.; Crusz, Shanika A.; Diggle, Stephen P. (Nature Publishing Group, 2015)
Staphylococcus aureus is historically regarded as a non-motile organism. More recently it has been shown that S. aureus can passively move across agar surfaces in a process called spreading. We re-analysed spreading motility using a modified assay and fo- cused on observing the formation of dendrites: branching structures that emerge from the central colony. We discovered that S. aureus can spread across the surface of media in struc- tures that we term ‘comets’, which advance outwards and precede the formation of dendrites. We observed comets in a diverse selection of S. aureus isolates and they exhibit the following behaviours: (1) They consist of phenotypically distinct cores of cells that move forward and seed other S. aureus cells behind them forming a comet ‘tail’; (2) they move when other cells in the comet tail have stopped moving; (3) the comet core is held together by a matrix of slime; and (4) the comets etch trails in the agar as they move forwards. Comets are not con- sistent with spreading motility or other forms of passive motility. Comet behaviour does share many similarities with a form of active motility known as gliding. Our observations therefore suggest that S. aureus is actively motile under certain conditions.